The Reflection of the Artistic Image of Growing Up on Boys and Girls Ideas About the Future - N.P. Shilova (Психолого-педагогические исследования)
The results of a study aimed at studying the ideas of growing up and the future in adolescents, boys and girls, are shown. The main purpose of the study was to identify the connection between life events that are significant for young people and their ideas about growing up, which is shown through the image of growing up in a feature film. The hypothesis was based on the assumption that the significance of life events in ideas about the future of boys/girls differs depending on the ideas of growing up based on the assessment of an artistic image. In total, the sample consisted of 1394 adolescents and young people aged 14 to 23 years (M=17; SD=2). Statistically significant differences were revealed in the ideas about the future of adolescents, boys and girls, with different types of ideas about growing up, revealed through an artistic image. Respondents who differ in the type of ideas about growing up show differences in the perspective of the future in relation to events related to "other people", "ideal objects" and the time period of the "open present". It was also found that there are differences in the significance of life events related to education, professional activity and communication among young people with different types of ideas about growing up based on an artistic image. These results may be useful for understanding the differences in the motivation of young people and for developing support and orientation programs in the process of growing up.